COMPARISON OF ANTIOXIDANT ACTIVITY BETWEEN SOCLETATION AND MACERATION EXTRACTION METHOD ON BINJAI LEAF EXTRACT (Mangiferacaesia) - Norliyanti Norliyanti; Irham Taufiqurrahman; Bayu Indra Sukmana (FKG Unlam, 2018)
Background :Wound is known to generate free radicals in inflammatory phase by the initiation of inflammatory cells such as polymorphonuclear. This cell is in function to destroy bacteria and viruses that are present in the wound. However, free radicals can also damage normal tissues when the amount of the accumulation is too much. Antioxidants are the ingredients that can eliminate free radicals throughchemical reaction so the formation of free radicals can be reduced. Binjai (Mangiferacaesia) is a plant that can produce natural antioxidants that are able to protect the body against the damage which caused by free radicals. The antioxidants in the leaves can be obtained by maceration and socletation extraction techniques. Purpose: To determine the difference between socletation and maceration extraction method towards antioxidant activity of binjai leaf ethanol extract as a preliminary study of binjai leaf antioxidant effect on wound healing. Methods: This research was pure experimental study(true experimental) with post-test only control group design, consisting of two treatment groups: maceration extraction methods group, socletation extraction methods group, and one control of ascorbic acidgroup. Measurement of antioxidant activity using DPPH method were measured by using a UV-Visspectrophotometry then IC50 values were calculated to determine the antioxidant activity. Results: Average IC50 values obtained fromthe socletation extract group was 50.791 ppm, while the maceration group was 60.135 ppm, and the control group was 13.825 ppm. Post Hoc LSD test result showed that the three groups had significant difference in each treatment.Conclusion:Based on this research, it can be concluded that binjai leaf extraction using socletation methods produce more powerful antioxidant activity compared to maceration method.